Asuhan Keperawatan pada Pasien Diabetes Melitus Tipe 2, Fase Akut dengan Pendekatan Model Adaptasi Roy: Studi Kasus - Neng Intan; Debbie Dahlia; Dikha Ayu Kurnia (Jurnal Keperawatan Silampari, 2022)
This study aims to describe nursing care in patients with diabetes mellitus in the acute phase, using the Roy application theory model. This type of research is a case study. The results showed that after nursing interventions were carried out in the form of diet education and adherence to therapy management, blood sugar control improved, client and family understanding increased, treatment days did not extend. In conclusion, the right way that nurses can prevent the recurrence of diabetes patients is to educate as early as possible on how to regulate nutrition through eating patterns with proper diet control and education on correct therapy management compliance. Keywords: Diabetes Mellitus, Diet, Education, Insulin